Inheritance of Hereditary Persistence of Fetal Haemoglobin (HPFH) in a Family of Western Odisha, India - Patel, Siris (J Clin Diagn Res, 2015)
Hereditary persistence of foetal haemoglobin (HPFH) is a rare inherited haemoglobin disorders in India. We encountered five cases of HPFH-3 in heterozygous condition in a single family of western Odisha, India. All the cases had raised % HbF (26.1±3.23%) with pancellular distribution of HbF in erythrocytes. There were no abnormalities found in the red cell indices. All the cases were asymptomatic till date with normal growth and development. Molecular confirmation of this haemoglobin disorders is important for control and prevention of haemoglobinopathies in this region.